Dietary polyphenols and chromatin remodeling. Issue 12 (13th August 2017) - Russo, Gian Luigi; Vastolo, Viviana; Ciccarelli, Marco; Albano, Luigi; Macchia, Paolo Emidio; Ungaro, Paola
ABSTRACT: Polyphenols are the most abundant phytochemicals in fruits, vegetables, and plant-derived beverages. Recent findings suggest that polyphenols display the ability to reverse adverse epigenetic regulation involved in pathological conditions, such as obesity, metabolic disorder, cardiovascular and neurodegenerative diseases, and various forms of cancer. Epigenetics, defined as heritable changes to the transcriptome, independent from those occurring in the genome, includes DNA methylation, histone modifications, and posttranscriptional gene regulation by noncoding RNAs. Sinergistically and cooperatively, these processes regulate gene expression by changing chromatin organization and DNA accessibility. Such induced epigenetic changes can be inherited during cell division, resulting in permanent maintenance of the acquired phenotype, but they may also occur throughout an individual life-course and may ultimately influence phenotypic outcomes (health and disease risk). In the last decade, a number of studies have shown that nutrients can affect metabolic traits by altering the structure of chromatin and directly regulate both transcription and translational processes. In this context, dietary polyphenol-targeted epigenetics becomes an attractive approach for disease prevention and intervention. Here, we will review how polyphenols, including flavonoids, curcuminoids, and stilbenes, modulate the establishment and maintenance of key epigenetic marks, thereby influencing gene expression and, hence, disease risk and health.